Running economy, maximal lactate steady state, and VO2max in highly trained Turkish distance runners - Shahidi, S. H. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Running economy (RE), Maximal Lactate Steady State (MLSS), and maximal oxygen uptake (VO2max) are pivotal factors influencing endurance running performance. Purpose: This study aimed to evaluate RE, MLSS, and VO2max across varying submaximal and maximal speeds, employing both oxygen cost (ml/kg/km) and caloric unit cost (kcal/kg/km) metrics in a cohort of highly trained male distance runners. It was hypothesized that caloric unit cost would afford greater sensitivity to speed-induced changes in running economy than traditional oxygen cost measurements, owing to its capacity to account for substrate utilization disparities.